Beyond Conservation: Tesso Nilo National Park, Climate Change, and Indonesia's Environmental Diplomacy - Purwasandi; Wahyudi, Herry (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2026)
This article examines Tesso Nilo National Park (TNTN) in Riau Province as a critical case study of the failure of subnational climate and environmental governance in Indonesia. The real-world situation in TNTN reveals a stark gap between diplomatic rhetoric and implementation on the ground. The proliferation of illegal oil palm plantations, massive deforestation, and recurring forest fires have reduced natural forest cover to less than 20 percent, released billions of tons of stored carbon, and eroded critical habitat, including for Sumatran elephants. The study adopts a qualitative case study design focused on TNTN, drawing on policy documents, government reports, NGO publications, and academic literature. The analysis is framed by the concepts of environmental diplomacy, multi-level governance, and climate governance failure. The findings suggest that weak vertical coordination, large-scale land-use changes driven by corporate and local actors, and increasing human-wildlife conflict reveal a systemic failure in translating national and international climate and conservation commitments into local outcomes. Therefore, the park represents a significant gap in Indonesia's environmental diplomacy efforts. In response, this article proposes an alternative, bottom-up model of environmental diplomacy that strengthens local actors through community-based conservation, community-based ecotourism, and broader civil society participation in decision-making.